ff->0/Z Collision in the Randall-Sundrum Model - Dao, Thi Le Thuy (H. : ĐHQGHN, 2017)
The Randall-Sundrum (RS) model is one of the most attractive candidates to solve the gauge hierarchy problem in the Standard Model (SM). This is a model in five-dimensional space time with a warped extra spatial dimension compactified on the orbifold S1/Z2. This paper studies the production of the radion and Z boson in the collision process with the polarization of the beams. The study results show that the value of the differential cross-section is the greatest when the angle between the direction of the beam radion and beam approximately 90 degrees for and 180 degrees for . Based on the results, it is expected that the reaction can give observable cross-sections in Larger Hadron Collider (LHC) at a high degree of polarization